Relationship between Duffy blood groups genotypes and malaria infection in different ethnic groups of Choco- Colombia (2012)
ABSTRACT: Introduction: The negative homozygous condition for the Duffy blood group (Fy-/Fy-) confers natural resistance to Plasmodium vivax infection. In this direction, studies carried out in Colombia are scarce Objective: To describe the relationship between Duffy genotypes in three ethnic communities in La Italia (Chocó) and malaria infection. Methods: A descriptive, cross-sectional study in symptomatic and asymptomatic malaria subjects. Sample size : Afro American, 73; Amerindian (Emberá) 74, and Mestizo, 171. Presence of Plasmodium infection was assessed by thick smear and the status of the Duffy gene by PCR and RFLP in order to identify the substitutions T-46C y A131G which origin the genotypes T/T, T/C , C/C y G/G, G/A, A/A. Results: Infection by Plasmodium was detected in 17% with 62% due to P. falciparum and 27% to P. vivax. Duffy genotypes were significantly associated to ethnicity (p= 0.003). Individuals with the C/C, A/A diplotype were exclusively infected by P. falciparum, whereas other diplotypes were infected with either species. In the Amerindian and Mestizo populations, the frequency of the T-46 allele was 0.90-1.00, among Afrocolombians this was 0.50, equal to the C allele and with absence of heterozygous At locus 131, the highest frequency of the G allele was 0.30 in Amerindians and the allele A was 0.69 in Afrocolombians. Conclusions: In the Amerindian and mestizo populations studied, a predominance of the allele T-46 (FY+) was observed, but P. vivax was not the most common. Infection by P. vivax was out ruled in all FY- individuals.